Chiral phosphapalladacycles as efficient catalysts for the asymmetric hydrophosphination of substituted methylidenemalonate esters : direct access to functionalized tertiary chiral phosphines - Pullarkat, Sumod A. (2013)
A chiral palladacycle-promoted enantioselective asymmetric hydrophosphination of substituted methylidenemalonate esters using diphenylphosphine that provides direct access to chiral tertiary phosphines is reported. Screening of three easily accessible C,N and C,P palladacycles as catalysts for this synthetic scenario provided insights into critical factors in catalyst design that influence the activation and stereochemistry in Pd(II)-catalyzed asymmetric P–H addition reactions involving such activated substrates.